Analisis Transpor Sedimen Dasar Sungai Alopohu yang Bermuara di Danau Limboto - Asri, A.A.O.; Husnan, R.; Utama, K.A. (Tadulako University, 2025)
One of the causes of flooding in Gorontalo is the reduced capacity of Lake Limboto, which has served as a natural water reservoir and flood preventer, to perform these functions effectively due to siltation. This diminished capacity is attributable to the deposition of sedimentary material carried by the rivers that drain into Lake Limboto. A total of 23 rivers discharge into Lake Limboto, contributing sedimentation on an annual basis. Among these, the Alopohu River is one of the most significant contributors. The objective of this study was to quantify the sediment transport generated by the Alopohu River. The analysis was conducted through the collection of direct measurement observation data in the downstream region of the Alopohu River, with the objective of obtaining data on river geometry, flow velocity, instantaneous discharge, and bottom sediment samples. Laboratory tests were conducted on basic sediment samples in order to ascertain the characteristics of the sediment grains. The data were subsequently analyzed using empirical formulas, namely the Meyer-Peter and Muller, Einstein, and Frijlink formulas. The quantity of bed sediment transport (bed load) in the downstream Alopohu River, as determined by discharge measurements and the application of the Meyer-Peter and Muller formula, is 2.86 tons per year. The Einstein formula yields a value of 621 tons per year, while the Frijlink formula produces a result of 54.67 tons per year. The discrepancy in the calculated values for each empirical formula is attributed to the specific parameters utilized in each formula